Neonatal Hemostasis Disorders: Bleeding and Thrombosis - Guaragni, Brunetta; Motta, Mario (International Journal of Pediatrics and Child Health, 2020)
Neonatal bleeding or thrombosis are serious problems and life threatening events. The diagnostic approach needs to consider the theory of the “developmental hemostasis” for interpreting blood tests. The causes, diagnosis and management of the main neonatal hemostatic abnormalities will be reviewed.